De professor a reitor: Nicácio Lopes em perfil - Sousa, Filipe Francilino de (2019)
This study used theoretical and methodological framework of the book report targeting the teacher Cícero Nicácio do Nascimento Lopes, Rector of the Federal Institute of Paraíba (IFPB). This journalistic product is the result of a two-year- research (2017/2019) for my Master Degree in Journalism dissertation. The book was based on literary journalism, where narrator takes part on the described environment, by using capturing, writing and text edition resources with humanized contents about things that happening in real life. It is also used profiles techniques involving biographycal issues and presenting different moments of his life by using interviews, overdetailed moments recording and the narration of someone´s life events that are great enough to be told. Nicacio Lopes is one of those men which have a strong past, present and future, and more specifically future: because he used to learn about his past to live the present and build the future. This journalistic product exhibits the daily life of a modern Rector. It also presents the beautiful journey of a public manager who became Rector of University and a great human being. It shows the tightened grip and the willingness that we need to be a modern Rector. The strong point of this work is the possibility of the reader seeing himself through the likenesses mirror.